2021
DOI: 10.1007/s00259-021-05233-2
|View full text |Cite
|
Sign up to set email alerts
|

Baseline PET/CT imaging parameters for prediction of treatment outcome in Hodgkin and diffuse large B cell lymphoma: a systematic review

Abstract: Purpose To systematically review the literature evaluating clinical utility of imaging metrics derived from baseline fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) for prediction of progression-free (PFS) and overall survival (OS) in patients with classical Hodgkin lymphoma (HL) and diffuse large B cell lymphoma (DLBCL). Methods A search of MEDLINE/PubMed, Web of Science, Cochrane, Scopus and clinicaltrials.gov dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 58 publications
0
46
1
1
Order By: Relevance
“…Frood et al investigated the role of baseline nuclear medicine imaging in the prediction of treatment outcome in Hodgkin and diffuse large B cell lymphoma [198] and concluded that further work in harmonization, segmentation and performance cut-off is required to develop robust methodologies that are amenable for clinical utility.…”
Section: Texture Analysis and Prognosis-focus On Other Cancersmentioning
confidence: 99%
“…Frood et al investigated the role of baseline nuclear medicine imaging in the prediction of treatment outcome in Hodgkin and diffuse large B cell lymphoma [198] and concluded that further work in harmonization, segmentation and performance cut-off is required to develop robust methodologies that are amenable for clinical utility.…”
Section: Texture Analysis and Prognosis-focus On Other Cancersmentioning
confidence: 99%
“…The currently available prognostic indicators fail to identify high-risk patients [ 4 , 5 ]. Therefore, it is urgently necessary to identify patients with a low or high risk of recurrence [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is concordant with a few earlier studies that evaluated a similar question, including rst order parameters such as SUVmax. For example, Frood et al [27] recently published a meta-analysis for baseline PET/CT imaging parameters as predictor of treatment outcome in Hodgkin and diffuse large B-cell lymphomas (DLBCL). In the metaanalysis 10 studies assessing SUVmax as predictor of response, however, none none of the studies evaluated radiomics features.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that radiomic biomarkers can be developed and crossreferenced with established clinical cellular and molecular biomarkers to better predict outcomes and in uence evidence based clinical decision making in patients with lymphoma. [22][23][24][25][26][27][28][29][30] The aim of this study is to evaluate the prognostic value of joint PET-and CT radiomics combined with standard clinical parameters in patients with HL. We hypothesize that some hidden radiomics features content within the baseline PET/CT may predict survival outcomes.…”
Section: Introductionmentioning
confidence: 99%